Exploring the managerial perspective on developing a new sport team brand - Melissa Davies; Matt Blaszka; Cole Armstrong (Journal of Applied Sports Management, 2023)
In recent years, research examining new sport teams has emerged. A total of ten senior sales and market executives were interviewed from recent expansion teams from Major League Soccer (MLS) to analyze team brand development for this study due to its continued expansion efforts across North America and the fact that the MLS continues to compete for market share against other “Big Four” sport teams in their respective cities. Utilizing content analysis, findings from this study identified four themes when developing a new team brand. These themes were Market Research, Soccer Culture, Brand Associations, and Supporter-Led Initiatives. Practical implications are provided for developing a new team brand.
Keywords: team brand; professional sports; brand equity; brand associations; marketing